Ultrasound Increases Flow through Fibrin Gels - Siddiqi, Farhan; Blinc, Ales; Braaten, Julie; Francis, Charles W (Thrombosis and Haemostasis, 1995)
Ultrasound accelerates fibrinolysis in vitro and in animal models of thrombosis. Since transport of fibrinolytic enzymes into clots by permeation may be an important determinant of the rate of fibrinolysis, we examined the effect of ultrasound on permeation through fibrin gels in vitro. Gels of purified fibrin were prepared in plastic tubes, and the rate of pressure-mediated fluid permeation was measured. Exposure to 1 MHz ultrasound at 2 W/cm2 and a duty cycle of 5 msec on, 5 msec off resulted in a significant (p = .005) increase in flow through the gel of 29.0 ± 4.2% (SEM). The ultrasound-induced flow increase was intensity-dependent, increasing from 17.0 ± 1.2% at 1 W/cm2 to 30.1 ± 1.9% at 2.3 W/cm2. Increased flow was not due to heating, detachment of fibrin from the tube wall or fragmentation of the gel resulting in channeling. However, degassing the fluid by autoclaving significantly reduced the ultrasound-induced increase in flow. We conclude that exposure of fibrin gels to ultrasound increases pressure-mediated permeation. This effect may be related to cavitation-induced changes in fibrin gel structure, and could contribute to the accelerated fibrinolysis observed in an ultrasound field.